2019
DOI: 10.1007/s11060-019-03152-9
|View full text |Cite
|
Sign up to set email alerts
|

NRG brain tumor specialists consensus guidelines for glioblastoma contouring

Abstract: ; 312.926.2520. TJK and WRB were responsible for statistical analyses Compliance with ethical standards: Conflict of interest: WRB's reports travel expenses from AAPM, and honoraria from Augmenix Inc. These do not pertain to this work and WRB declares he has no conflict of interest with regard to this study. TJK is on a speaker's bureau for AstraZeneca, has served as a consultant to Varian Medical Systems and was on an advisory board for Abbvie Inc. These do not pertain to this work and TJK declares he has no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…The debate is over whether it is necessary to treat all possible tumor microinvasion locations. The theoretical basis for including peritumoral edema is that the edema area may be an infiltrative area ( 6 , 7 ). The theoretical basis for excluding edema is that there is no significant difference in recurrence patterns either with or without edema.…”
Section: Introductionmentioning
confidence: 99%
“…The debate is over whether it is necessary to treat all possible tumor microinvasion locations. The theoretical basis for including peritumoral edema is that the edema area may be an infiltrative area ( 6 , 7 ). The theoretical basis for excluding edema is that there is no significant difference in recurrence patterns either with or without edema.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ESTRO-ACROP GBM guideline, although providing a detailed expert consensus of target delineation, lacked quantitative analyses of inter-observer contour variability [9]. Finally, Kruser et al recently reported an NRG brain tumor specialist consensus report on GBM contouring, which highlighted several similar findings with respect to limiting the CTV to anatomical boundaries such as the falx, the tentorium cerebelli, and extension of the CTV across the commissural pathways and into the brainstem [8]. However, the NRG study was limited by only a few study cases (4 GBM cases in total) and, therefore, tumor locations.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our study compare favorably to other glioma delineation studies. For example, the Korean Radiation Oncology Group observed considerable variability amongst 15 radiation oncologists’ contours of GTVs and CTVs (mean kappa 0.58 and 0.65, respectively) in 9 cases of newly diagnosed GBM patients [ 10 ], and the recently reported NRG consensus contouring study by 10 radiation oncologists of 4 GBM cases using a two-dose-level approach reported a kappa statistics range from 0.59 to 0.81 for high and low dose GTVs, and 0.72 to 0.85 for high and low dose CTVs [ 8 ]. In our study, the largest variability was observed in case 4, which illustrated a pineal/thalamic GBM with inferior extension to the superior midbrain and posterior abutment of the tentorium cerebelli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target volume definition of GBM varies remarkably at different institutions worldwide as a result of contradictory recommendations. The use of several MRI sequences at different time points, including preoperative MRI with a diffusion-weighted sequence for tractography and functional MRI, thereafter MRI within 48 hours post-surgery and a further pre-RT MRI, has recently become a standard requirement (30).…”
mentioning
confidence: 99%